Laser-Beam Interactions with Materials : Physical Principles and Applications - Allmen, Martin (Springer series in materials science, 1995)
Laser-Beam Interactions with Materials treats, from a physicist's point of view, the wide variety of processes that lasers can induce in materials. Physical phenomena ranging from optics to shock waves are discussed, as are applications in such diverse fields as semiconductor annealing, hole drilling and fusion plasma production. The approach taken emphasizes the fundamental ideas and their interrelations. The newcomer is given the necessary important background material, while the active research worker finds a critical and comprehensive review of the field.